Multiprobe Microwave Multimeter Error Definition on Its Sensor Error Base - Volkov, V. M.; Zaichenko, O. B.; Yevdokimov, V. V. (Publishing House ”Izvestiya Vuzov”, 2005)
This paper propose a new method of estimation of multiprobe microwave multimeter algorithms precision by mean of accumulation of partial error. The least square solution is used for variance and covariance matrix definition. The weighted coefficient is obtained from algorithms derivatives with respect to intermediate variable. Substituting the expression for standard deviation (variance) end weighted coefficient in formula for partial error accumulation we can compare different algorithms, study frequency properties of algorithms.
Keywords: microwave sensors; reflection; least squares methods; nonlinear equation; covariance matrix